HOMEPAGE MAKING PUBLIC HIGH SCHOOL CULTURE USING HTML JAKARTA - Yuli Wahyono; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2001)
With the high school homepages Cultural made for the first time, this could be a good tool to promote and inform the existence of high school culture in which terdapt positive activities to support better education. The existence of this homepage can also be utilized by the wider community, as well as high school students about the culture and the alumni-alumni-school as a venue for the reunion.